Efficient algorithms for optimal pickup-point selection in the selective pickup and delivery problem with time-window constraints - Yosuke TAKADA; Masaru SHIMAZAKI; Yannan HU; Mutsunori YAGIURA (Journal of advanced mechanical design, systems, and manufacturing, 2020)
We address the selective pickup and delivery problem with time-window constraints, which is a problem of finding vehicle routes that pick up commodities at stores and deliver them to customers so as to minimize the total distance of the routes under capacity and time-window constraints. In this paper, to design a local search method for this problem, we consider the following: Given the order of customers in a route, we determine the pickup stores and optimal times of visiting at customers so that the total distance is minimized. This is called the optimal pickup point problem and is a subproblem of the selective pickup and delivery problem with time-window constraints. We show that the optimal pickup point problem is NP-hard in general, and then we propose dynamic programmingmethods, which can obtain upper and lower bounds in linear time, and optimal solution in pseudo-polynomial time.